A theoretical and experimental investigation of erosion prone areas on the blade surfaces of a centrifugal impeller handling granular solids. - Ahmad, Khaled (Cranfield University, 1982)
The erosion prone areas on the blade surfaces of a centrifugal impeller handling granular solids have been investigated both theoretically and eperimentally. The objective of the theoretical study is to develop software to predict the erosion prone areas on the blade surfaces of a slurry handling impeller. The basic concept in the theoretical study has been to find the particle trajectories inside the impeller. The governing equations of the motion of particles within the impeller are solved in a stepwise manner with time for a given flow field. The flow field is calculated by solving the conservation equations for the flow, using a finite difference method. The number density of the particles in the cross-section of the pipe through which the particles enter the impeller is calculated by applying a discretization procedure to the insitu concentration profile of the particles. The damage to the surface caused by impacting particles is estimated by calculating the velocity and the angle at which the particles impact on a surface. The material property of the particle or the surface does not explicitly enter into calculations. It is shown that for a given combination of particles and surface material, the material property of the particles and the surface can be isolated. In this way a relative measure of the depth of volume loss at different positions of the surface can be calculated. The surface can then be divided into a number of erosion prone areas. The model is tested by undertaking a number of experiments using a commercially available slurry pump which handled a mixture of fine pea gravels in water. The predicted erosion pattern suggested the area near the leading edge to be the most erosion prone zone. The agreement with the experimental results in this respect was satisfactory. The extent of the erosion zone on the blade surface as suggested by the analytical model was in close agreement with the experimental values. The analytical model also suggested that the major part of the erosion areas would lie near the back shroud of the impeller. This was in close agreement with the experimental results.
Keywords: Blade; erosion; granular solids; impeller; trajectories; flow; surface